TABOO AND SWEAR WORDS IN HEARTBREAK HIGH SERIES - RAHIM, ABDUL; KHAIRANI, FAUZIAH (LINGUISTICA, 2024)
This study aims to identify the types of taboo and swear words and analyze their realization by the main characters in the Heartbreak High Series. This study utilizes a descriptive qualitative method, extracting data from the series, in the form of utterances, dialogues, and conversations that contain taboo and swear words. The findings revealed that four types of taboo words found in the Heartbreak High series realized by the main characters: lavatory (28%), private parts of the body (11%), religion (9%), sexual activity (43%), with an additional (9%) that does not align with Swan™s theory (1995). Additionally, this study categorizes swear words in the series into two categories. First are strong swear words, and second is weak swear words. Strong swear words consist of exclamations of annoyance (17%), exclamations of surprise (8%), exclamations of unconcern (2%), insults (33%), insulting request to go away (9%), emphasize an emotion (25%), surprise question (5%) and violent refusal/rejection (1%). Weak swear words consist of exclamations of annoyance (18%), exclamations of surprise (46%), and exclamations of emotion (36%). The emotional conditions of the main characters while using the swear words are joy, surprise, sadness, anger, fear, and hatred.